2013
DOI: 10.1021/jp404107j
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of the Structure and Electronic Circular Dichroism Spectroscopy of Blue Copper Proteins

Abstract: The calculation of the electronic circular dichroism (CD) spectra of the oxidised form of the blue copper proteins plastocyanin and cucumber basic protein and the relationship between the observed spectral features and the structure of the active site of the protein is investigated.Excitation energies and transition strengths are computed using multi reference configuration interaction, and it is shown that computed spectra based on coordinates from the crystal structure or a single structure optimised in quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
(96 reference statements)
0
9
0
Order By: Relevance
“…In this state, the protein has a rich spectroscopy, and has been studied by several different spectroscopic techniques including electronic absorption, circular dichroism, magnetic circular dichroism, and x‐ray absorption spectroscopies . Alongside these experimental measurements there have been numerous theoretical studies with a wide variety of different levels of approximation . These studies have led to an understanding of the nature of the observed spectroscopic features and detailed insight into the electronic structure of the active site.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this state, the protein has a rich spectroscopy, and has been studied by several different spectroscopic techniques including electronic absorption, circular dichroism, magnetic circular dichroism, and x‐ray absorption spectroscopies . Alongside these experimental measurements there have been numerous theoretical studies with a wide variety of different levels of approximation . These studies have led to an understanding of the nature of the observed spectroscopic features and detailed insight into the electronic structure of the active site.…”
Section: Introductionmentioning
confidence: 99%
“…The studies of the strain energy and the reorganization energy have been largely based on a static view of the structures. It is known that conformational averaging is important in determining the properties of these proteins . In this article, we develop a more dynamic picture of the electron transfer process.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations